DAMPAK PENETAPAN BATAS USIA CAPRES DAN CAWAPRESTERHADAP PROSES DEMOKRASI DI INDONESIA: ANALISIS PUTUSAN MK RI NO. 104/PUU-XII/2023 - Saqinah Aifi Kirmala; Rima Volyna Munthe, Ruth Hanna Apriani Sihombing, Silvia Mahrani, Solavide Ginting, Tebi Tafianta Ba (JOURNAL OF LAW AND NATION, 2024)
The minimum age requirement for candidates running for president and vice president has changed as a result of the Republic of Indonesia's Constitutional Court's judgment (number 104/PUU-XXI/2023). This decision is an important step in ensuring that candidates have the right qualifications to lead a country. This study aims to examine the implications and impacts of the age limit on the democratic process and leadership in Indonesia. The method used in this research is a qualitative method with a normative juridical approach through literature study. The data collection technique in this research is by analyzing the literature, decisions of the constitutional court, books, scientific articles, and various other scientific reading sources related to the material discussed in this study, namely the Age Limit for Presidential / Vice Presidential Candidates (Legal Analysis of MKRI Decision No. 104 / PUU-XII / 2020). As per Law Number 7 of 2017 respecting General Elections (Election Law), Article 169 letter q, five applications cannot be accepted regarding the age limit of presidential and vice presidential candidates (presidential and vice presidential candidates). Case Numbers 102/PUU- XXI/2023, 104/PUU-XXI/2023, 107/PUU-XXI/2023, 96/PUU-XXI/2023, and 93/PUU-XXI/2023 were discussed. The Decision Enunciation Session was held on Monday, October 23, 2023, in the Plenary Session Room of the Constitutional Court of Republik of Indonesia. Following the ruling of the Constitutional Court (No. 104/PUU-XXI/2023), it has brought changes in the interpretation and application of the minimum age limit for presidential and vice presidential candidates with significant implications for future elections.